Stadtrandsiedlungen und Industrialisierung in Taipei, Taiwan - Koch, Wilfried (ERDKUNDE, 1976)
This small-area analysis seeks to investigate and interpret suburban developments in Sanchung/Taipei as an example of growth forms and conditions in industrializing suburban settlements throughout Taiwan. In spite of unfavourable natural conditions the number of inhabitants in Sanchung has increased ten-fold over the past 25 years, the majority of inhabitants being young migrants from the rural districts of the western coastal plain. House forms are characterized by the comprehensive adoption of the Western apartment house. In this regard a periphery/centre differentiation has developed, which runs parallel to that of a functional sort (Photo 3 and 5). The intermingling and close penetration of the twin func tions of dwelling and working are characteristic. Small scale industrial concerns are widespread, being absent only in the central business district. The commercial usage of the groundfloor of almost every other building is striking (fig. 2). Thus the migrants who settle in the suburbs are not only consumers but also producers - that is, economically active.